MENGENANG SERATUS TAHUN SCHUMACHER FILSUF EKONOMI YANG HUMAN-EKOLOGIS - Armawy, Armaidy (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2008)
AbstractThis paper wants to remind of Schumacher’s thought in order tocelebrate of one hundred years of his birthday. From his philosophical thought we are able to hope a fresh thought that bring human being to an enlightenment to go out from uncertainty life as an effect of science and technology. Schumacher was an amateur in economics who struggle in underground arena; he was popular for his concern to common people. He used eastern economic tradition that came from Buddhism and Gandhi’s thought that concern to common people interest. He also tried to realize his ideas in the concrete life. It was made him as a pioneer in the concept ofmiddle and appropriate technology. Small is Beautiful was hismasterpiece beside many other writings; however, if we retrace his works, all of his writing was a unity. We can not differentiatewhich one a philosophical view and other economical view are, for he gave the same attention—freedom to human being in his activities and creativities.Keywords: Schumacher, economic, philosophy, and commonpeople.